2008
DOI: 10.1309/4dxeafg2jxyf34n3
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Two Methods to Determine the Presence of High-Risk HPV Cervical Infections

Abstract: Clinical tests for human papillomavirus (HPV) DNA require clinical validation before being offered for use by laboratories. To determine the clinical viability of a laboratory-developed test using the Invader HPV reagents (Third Wave Technologies, Madison, WI), a retrospective study was designed using 213 patient cervical cytologic samples. The results of the Invader assay were directly compared with the results obtained using the Hybrid Capture 2 High-Risk HPV assay (Digene, Gaithersburg, MD). The results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 30 publications
2
22
0
Order By: Relevance
“…Other studies published from a laboratory (2)(3)(4)(5)(6) or clinical (7) perspective do not reflect this opinion. In this letter, we compare a large data set generated from consecutive 9-month intervals of HC2 and Cervista screening, stratified by age and cytological classification.…”
mentioning
confidence: 94%
“…Other studies published from a laboratory (2)(3)(4)(5)(6) or clinical (7) perspective do not reflect this opinion. In this letter, we compare a large data set generated from consecutive 9-month intervals of HC2 and Cervista screening, stratified by age and cytological classification.…”
mentioning
confidence: 94%
“…This assumption is supported by previous studies that reported occasional false-negative results for hc2 when comparing hc2 and Invader-based assays. 11,14,15 In addition, results from nearly one-third of the cytologically unsatisfactory samples in the Cervista population could not be reported because of low internal control signal; however, all samples of this type from the hc2 population that had sufficient volume for testing were reported as being definitively positive or definitively negative for HR-HPV. The clinical usefulness of HR-HPV testing largely relies on its high sensitivity and strong negative predictive value; thus, false-negative results are of particular concern because they fail to identify women who require further testing.…”
Section: Discussionmentioning
confidence: 99%
“…Interference or inhibition was not observed with any of the tested substances that may be present in cervical specimens [40]. In four studies, which included a total of 1248 samples, different prototypic Review versions of Cervista showed 81.6-90.8% agreement with hc2 [33,[41][42][43]45]. After testing 12,490 specimens using Cervista assay prototype Invader V2.0, Harvey et al recently assessed the clinical performance of this prototype assay by comparison of obtained HPV results with corresponding biopsy results for a total of 1931 cases [44].…”
Section: Cervista Hpv Hr Testmentioning
confidence: 93%
“…To the best of our knowledge, eight evaluations have been published to date: one analytical [40] and seven evaluations comparing the performance of different prototypic versions of the current assay with other HPV assays, mainly hc2 [33,[42][43][44][45][46][47]. A study that characterized the analytical performance of an investigational use only version of Cervista showed that analytical sensitivity for the targeted 14 HPV types ranged from 1250 to 7500 copies per reaction, depending on the HPV type [40].…”
Section: Cervista Hpv Hr Testmentioning
confidence: 99%